2021
DOI: 10.2478/jvetres-2021-0015
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological safety of food of animal origin from organic farms

Abstract: The organic food sector and consumer interest in organic products are growing continuously. The safety and quality of such products must be at least equal to those of conventional equivalents, but attaining the same standards requires overcoming a particular problem identified in organic food production systems: the occurrence of bacterial pathogens such as Salmonella, Campylobacter, Listeria monocytogenes, Staphylococcus aureus and pathogenic Escherichia coli. These food-borne microorganisms were detected in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…[ 15 ]. Growth of foodborne pathogens such as Salmonella , and toxin-producing strains of E. coli , L. monocytogenes , C. perfringens, and S. aureus are the main concern with meat and poultry products [ 16 , 17 , 18 ]. These bacteria are the most common cause of foodborne illnesses.…”
Section: Introductionmentioning
confidence: 99%
“…[ 15 ]. Growth of foodborne pathogens such as Salmonella , and toxin-producing strains of E. coli , L. monocytogenes , C. perfringens, and S. aureus are the main concern with meat and poultry products [ 16 , 17 , 18 ]. These bacteria are the most common cause of foodborne illnesses.…”
Section: Introductionmentioning
confidence: 99%
“…in any of the samples analyzed. Sosnowski & Osek (2021) observed that despite reports by several authors about the presence of Listeria spp. in different organic and conventional matrices there is no significant difference between the production systems on the presence of Listeria spp.…”
Section: Resultsmentioning
confidence: 92%
“…Specifically, it has been found in studies based on biochemical analyses of egg composition that, compared to conventional eggs, organic eggs are lower in saturated fat (conventional eggs: 85.7 g kg−1 yolk; organic eggs: 68.1 g kg−1 yolk) (20), have a lower n-6/n-3 ratio (conventional eggs: 11.5; organic eggs: 7.8) (20), and have fewer endocrine disruptors such as dimethyl phthalate (DMP) (conventional eggs: 76%; organic eggs: 52%) (33). In addition, other review studies reported that organic eggs are less exposed to antibiotics (34) and are less contaminated by Salmonella (35). These biological differences are supposed to be largely explained by animal feed based on feed made with mostly organic products and under extremely hygienic conditions (29,36).…”
Section: Discussionmentioning
confidence: 99%